SYSTEM LITERATURE REVIEW: SELF-EFFICACY TERHADAP KEMAMPUAN PEMECAHAN MASALAH DALAM MENGERJAKAN SOAL HOTS DITINJAU DARI GAYA BELAJAR - Anggun; Abdul Aziz; Martyana Prihaswati (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2025)
The main objective of this study is to explore the relationship between self-efficacy, ability to solve mathematical problems, and higher level thinking skills (HOTS), by paying attention to the influence of learning style on the success of the learning process. This study uses the Systematic Literature Review (SLR) approach, which is conducted through searching literature from various scientific sources relevant to data collection using Google Scholar, published in the period 2020–2025. The study process is carried out through the planning, implementation, and reporting stages which include identification, selection, and this study also involves the analysis of articles that focus on subjects that meet the inclusion and exclusion criteria. The results of the study show that self-efficacy has a significant role in improving students' ability to solve mathematical problems that require high-level thinking skills (HOTS). Students with a high level of self-efficacy tend to have a more systematic sense of confidence, perseverance, and a more systematic mindset when facing complex problems. In addition, the effectiveness  of the influence of self-efficacy is influenced by the learning style and learning strategies applied. Students with learning styles that align with certain teaching methods show better performance in higher-level thinking. Therefore, effective mathematics learning must be arranged adaptively by integrating  strengthening self-efficacy, developing HOTS skills, and adjusting to students' learning styles. It is hoped that the results of this research can be a reference in designing learning strategies that are able to encourage continuous improvement in students' mathematical problem-solving abilities and critical thinking skills